Facile synthesis of PEI-based crystalline templated mesoporous silica with molecular chirality for improved oral delivery of the poorly water-soluble drug. (1st January 2021) - Xin, Wei; Wang, Yumei; Bian, Yan; Lin, Jiahui; Weng, Wenhao; Zhao, Xinyi; Gou, Kaijun; Guo, Xianmou; Li, Heran
Abstract: The aim of this study was to build up a novel chiral mesoporous silica called PEIs@TA-CMS through a facile biomimetic strategy and to explore its potential to serve as a drug carrier for improving the delivery efficiency of poorly water-soluble drug. PEIs@TA-CMS was synthesized by using a chiral crystalline complex associated of tartaric acid and polyethyleneimine (PEIs) as templates, scaffolds and catalysts. The structural features including morphology, size, pore structure and texture properties were systematacially studied. The results showed that PEIs@TA-CMS was monodispersed spherical nanoparticles in a uniformed diameter of 120–130 nm with well-developed pore structure (SBET : 1009.94 m 2 /g, pore size <2.21 nm). Then PEIs@TA-CMS was employed as nimodipine (NMP) carrier and compared with the drug carry ability of MCM41. After drug loading, NMP was effectively transformed from the crystalline state to an amorphous state due to the space confinement in mesopores. As expected, PEIs@TA-CMS had superiority in both drug loading and drug release compared to MCM41. It could incorporate NMP with high efficiency, and the dissolution-promoting effect of PEIs@TA-CMS was more obvious because of the unique interconnected curved pore channels. Meanwhile, PEIs@TA-CMS could significantly improve the oral adsorption of NMP to a satisfactory level, which showed approximately 3.26-fold higher in bioavailability, and could effectively prolong the survival time of mice on cerebral anoxia from 10.98 to 17.33 min.